Therapeutic effect and mechanism of combination therapy with ursolic acid and insulin on diabetic nephropathy in a type I diabetic rat model - Liu, Yang; Zheng, Jin-Yan; Wei, Zhi-Tao; Liu, Shu-Kun; Sun, Ji-Lei; Mao, Yin-Hui; Xu, Yong-De; Yang, Yong (Frontiers in Pharmacology, 2022)
This work aims to investigate the therapeutic effect of ursolic acid (UA) plus insulin on renal injury in streptozotocin (STZ)-induced T1DM rats. The experimental details are as follows: twenty-four Sprague–Dawley rats received one intraperitoneal STZ injection (60 mg/kg) and were randomized to receive vehicle gavage, continuous subcutaneous insulin infusion, or both UA (50 mg/kg) and insulin (n=8 each) after 4 weeks of modeling. Normal vector-treated rats served as controls (n=8). After 4 weeks, changes in renal function indices and pathological damage were assessed. Additionally, oxidative stress-, apoptosis-, and fibrosis-related proteins in kidney tissue were measured. Compared with the negative control group, the vehicle group showed higher levels of creatine, blood urea nitrogen, urinary protein, apoptosis, and lipid peroxidation, lower () superoxide dismutase levels, and worse pathological kidney damage. Better outcomes were achieved with the combined treatment than with the insulin-only treatment. ibrosis-related protein levels (TGF-β1, phosphorylated p38 MAPK) in renal tissue decreased more after the combination treatment than after the insulin-only treatment. This study shows that the combination of insulin and UA significantly improved the pathological changes in the renal tissue of T1DM rats, and the underlying mechanism is related to oxidation resistance and downregulation of the TGF-β1/p38 MAPK signaling pathway.